الحمـــــــاية الجزائيــــة للطفل من جرائـم الاستغلال الجنسي عبـر شبـكة الإنترنت - زهراء, بن عبد الله (Revue jurisprudence; Vol. 11 No 01 (2019): مجلة الاجتهاد القضائي, 2019)
The use of modern communications technology by all categories of society, especially the children who are fascnated by discovery, has exposed them to sexual exploitation via the internet, which poses a danger to the child’s behavior psychology and danger to seciety as a whole In view of the worsening of this heinous phenomenon throught the world, many international conventions called for an end to the crimes of sexual exploitation of childs and urge states to put in place strict laws to deter the perpetrators of these crimes and ensure the protection of children. the algerian legislator also introduced legal provisions in the pénal code and the child’s protection law act and punish the crimes of sexual exploitation of children.